Baús de saberes e de significações imaginárias: o lugar da infância na formação docente de três professoras egressas do curso de pedagogia - Irgang, Silvania Regina Pellenz (2009)
This research was developed and presented to the Post-Graduation Program in Education, Master s Degree of the Education Centre of Federal University of Santa Maria, Research Line Formation, Knowledges and Professional Development, aiming at identifying and analyzing knowledges and imaginary meanings concerning the place of childhood in the formative trajectory of three teachers from the Pedagogy course: two of them, related to Preschool Education and Pedagogical Disciplines of High School, and the other one, related to Early Childhood Education Licentiate s Degree, from Federal University of Santa Maria. This theme evolved based on the relationships I established through my professional experience as a teacher of Early Childhood Education, as well as through the investigations and discussions which took place in the research group about social imaginary, life stories and teachers knowledges, through teachers formative trajectories. In this sense, I found in formation-research the possibility to (re)signify the meanings concerning the place of childhood in teachers formation, in order to contribute with their ormation/self-formation and learning, both in initial formation and professional experience. Based on that, I resorted to a qualitative approach as a means to develop formative experiences and to semi-structured interviews, which allowed the participants to narrate their knowledges and imaginary meanings about the place of childhood in their formative trajectories. Both professional and experiential knowledges were crossed by personal knowledges through the participants life stories, as they narrated the meanings associated to their lives as children and to the infancies lived in the family, at school, in the streets, in different contexts, times and spaces. The work of memory was essential to the (re)construction of imaginary meanings, knowledges and places which allowed encounters and disencounters with childhood in teachers formation. It also helped, through collective memory, to develop teachers own recognition as the authors of their self-narratives in this process of research-formation. In their oral and biographical narratives, the place of childhood in the formative trajectory was marked by meanings which became present in the experiences with the children, in the knowledges produced in initial formation and in the work as formative teachers of those who choose Pedagogy as their professional field. The place attributed to childhood is fundamental for the child to (re)encounter playing, creativity, movement and experimentation with the different languages which must be available in the Pedagogy curriculum and at the Early Childhood Education school. This research-formation allowed the three teachers form the Pedagogy course to reflect about their own formative trajectories and the places themselves have made available to childhood in their contexts of personal and professional interventions.